2015
DOI: 10.1093/infdis/jiv112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Q211and K222PRNPPolymorphic Variants in the Susceptibility of Goats to Oral Infection With Goat Bovine Spongiform Encephalopathy

Abstract: These results demonstrate that transmission of goat BSE is genotype dependent, and they highlight the pivotal protective effect of the K222 PRNP variant in the oral susceptibility of goats to BSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…However, whether BSE-induced synaptic pathology in goats occurs in other localisations such as the brain remains unclear and has to be elucidated in future investigations. The lack of PrP Sc deposition in IRK/IRQ animals substantiates their low susceptibility to clinical BSE (Aguilar-Calvo and others 2015). In summary, the findings of the present study suggest that axonal damage and disturbed axonal transport in the spinal cord white matter might play a so far underestimated role in the pathogenesis of TSEs.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…However, whether BSE-induced synaptic pathology in goats occurs in other localisations such as the brain remains unclear and has to be elucidated in future investigations. The lack of PrP Sc deposition in IRK/IRQ animals substantiates their low susceptibility to clinical BSE (Aguilar-Calvo and others 2015). In summary, the findings of the present study suggest that axonal damage and disturbed axonal transport in the spinal cord white matter might play a so far underestimated role in the pathogenesis of TSEs.…”
mentioning
confidence: 86%
“…Following the discovery of goat BSE cases in the UK and France (Eloit and others 2005, Jeffrey and others 2006, Spiropoulos and others 2011) small ruminants were considered to pose a BSE infection risk/source for cattle, and human beings in particular. In goats experimental TSE susceptibility strongly depends on polymorphisms in the prion protein gene ( PRNP ) (Aguilar-Calvo and others 2014, 2015, Lacroux and others 2014). In particular, goats with R/Q 211 polymorphism (IQQ/IRQ; single-letter amino acid code) and Q/K 222 polymorphism (IRK/IRQ) show delayed or even absent clinical signs compared with wild-type goats (IRQ/IRQ) (Aguilar-Calvo and others 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental infection of goats with classical caprine scrapie the S127 variant have showed that it is not protective . The most recent studies have revealed that K222 conferred a strong but not absolutely protective effect against classical scrapie, but the K222 variant had a pivotal protective effect on the oral susceptibility of goats to BSE Aguilar-Calvo et al, 2015). Aguilar-Calvo et al (2014) showed that Tg K222 mice are susceptible to infections when inoculated with goat BSE isolates, even if transgenic mice expressing K222 allele are resistant to classical ovine scrapie and bovine BSE isolates.…”
Section: Role Of Prnp In Small Ruminantsmentioning
confidence: 99%